Berpikir Kreatif Dalam Fisika Dengan Pembelajaran Conceptual Understanding Procedures (CUPs) Berbantuan LKPD - Nurul Fitriani; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to improve students' creative thinking ability in physics by using conceptual understanding learning learning with LKPD. This quasi experimental study uses non-equivalent control group design. The population is all students of class X MA NW Narmada. The sample was chosen using purposive sampling technique which consist of class XB students as experiment class and XA class student as control class. The research instrument uses verbal and figural creativity tests that have been validated by experts. Hypothesis test using t-pooled variance test. Increased creativity is determined based on the results of the N-gain test. The results showed that there was an increase of students' creativity in both classes. Verbal and figural creativity improves in both classes. The experimental class experienced a higher creativity increase than the control class. Verbal creativity increased higher than the figural creativity. This shows that LKPD conceptual understanding procedure model applied successfully improve the creativity of learners in physics learning.